2016
DOI: 10.1016/s0140-6736(15)00725-4
|View full text |Cite
|
Sign up to set email alerts
|

Public health impact and cost-effectiveness of the RTS,S/AS01 malaria vaccine: a systematic comparison of predictions from four mathematical models

Abstract: SummaryBackgroundThe phase 3 trial of the RTS,S/AS01 malaria vaccine candidate showed modest efficacy of the vaccine against Plasmodium falciparum malaria, but was not powered to assess mortality endpoints. Impact projections and cost-effectiveness estimates for longer timeframes than the trial follow-up and across a range of settings are needed to inform policy recommendations. We aimed to assess the public health impact and cost-effectiveness of routine use of the RTS,S/AS01 vaccine in African settings.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
206
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(217 citation statements)
references
References 20 publications
8
206
0
3
Order By: Relevance
“…On the horizon, there are ways to use drugs and diagnostics in innovative campaigns to clear the human infectious reservoir (31), potential rollout of vaccines (32), coverage increases with existing tools (2), and more, which could get closer to elimination. However, it will require high levels of effort and funding just to maintain current gains, and the spread of pyrethroid resistance in mosquito vectors across much of Africa raises the question as to whether some of these achieved gains may in fact be reversed (33).…”
mentioning
confidence: 99%
“…On the horizon, there are ways to use drugs and diagnostics in innovative campaigns to clear the human infectious reservoir (31), potential rollout of vaccines (32), coverage increases with existing tools (2), and more, which could get closer to elimination. However, it will require high levels of effort and funding just to maintain current gains, and the spread of pyrethroid resistance in mosquito vectors across much of Africa raises the question as to whether some of these achieved gains may in fact be reversed (33).…”
mentioning
confidence: 99%
“…Four independent groups developed mathematical models to estimate the public health impact and cost-effectiveness of RTS,S/AS01 [47]. Data from the phase III trial were used to parametrize the models.…”
Section: Public Health Impactmentioning
confidence: 99%
“…In addition, public health impact modeling predicts that an important number of clinical and severe malaria cases and malaria deaths may be prevented by RTS,S/AS01, especially in moderate-to-high malaria transmission settings across sub-Saharan Africa. Four different models estimated that, over a 15-year time horizon, on average 1 death and approximately 230 clinical malaria cases might be prevented for every 200 children vaccinated with 4 doses of RTS,S/AS01 if implemented in regions with a P. falciparum parasitemia prevalence of 10% or more [47]. At a vaccine price of US$5 per dose, the cost per disability-adjusted life-year averted in these areas of moderate-to-high P. falciparum prevalence would be less than $100, an amount comparable to that of other malaria control measures [47].…”
Section: Expert Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, WHO is advised by the Strategic Advisory Group of Experts (SAGE) on Immunization to make global vaccine-related recommendations, with input from models that have been appraised by its advisory committee, the Immunization and Vaccines related Implementation Research Advisory Committee (IVIR-AC). Recently, the outputs of a coordinated mathematical model comparison of the potential impact of the RTS, S malaria vaccine were used in the decision-making process for WHO recommendations on the use of this vaccine [13,14]. The modelling revealed that despite the overall low efficacy, the vaccine could have a substantial additional public health impact across a broad range of settings representative of malaria parasite prevalence in Africa in the presence of other ongoing interventions.…”
Section: Role For Modelling In Shaping National and International Recmentioning
confidence: 99%